1998
DOI: 10.1007/bf02464058
|View full text |Cite
|
Sign up to set email alerts
|

Addition and reexamination of Japanese species belonging to the genus Cercospora and allied genera I. Collections from Nansei-lslands (1)

Abstract: In the first report of the present series, six species collected from Nansei Islands were discussed. Of these, one found on Elaeocarpusjaponica was described as a new species, Pseudocercospora elaeocarpicola. Pseudocercospora plumeriae on Plumeria rubra was transferred from the genus Cercospora and added to the Japanese fungous flora, together with Cercosporidium bougainvilleae on Bougainvillea spectabilis. One of the three remaining species, Pseudcercospora punicae on Punica granatum was newly recorded from N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Preliminary results of these studies in some Islands have been reported (Kobayashi 1996;Kobayashi and Kawabe 1991;Kobayashi and Nishijima 1995;Kobayashi and Watanabe 1995;Kobayashi et al 1990Kobayashi et al , 1994Kobayashi et al , 1998Kobayashi et al , 2001. Among the collected fungi, those belonging to the genus Cercospora and related genera were reported in succession in the other series (e.g., Kobayashi et al 1998;Nakashima et al 2002). For the other fungi, including new species and newly recorded species in Japan, a new series of articles is begun here.…”
Section: Introductionmentioning
confidence: 85%
“…Preliminary results of these studies in some Islands have been reported (Kobayashi 1996;Kobayashi and Kawabe 1991;Kobayashi and Nishijima 1995;Kobayashi and Watanabe 1995;Kobayashi et al 1990Kobayashi et al , 1994Kobayashi et al , 1998Kobayashi et al , 2001. Among the collected fungi, those belonging to the genus Cercospora and related genera were reported in succession in the other series (e.g., Kobayashi et al 1998;Nakashima et al 2002). For the other fungi, including new species and newly recorded species in Japan, a new series of articles is begun here.…”
Section: Introductionmentioning
confidence: 85%
“…on several Prunus species (Miyake, 1923;Katsuki, 1965;Kobayashi et al, 1998) Mycosphaerella fungus can be found in the original paper (Abe, 1937).…”
Section: Taxonomy Of the Causal Fungusmentioning
confidence: 96%
“…It has been well known as the pathogen of the leaf spot on Styrax japonica (Japanese name: Egonoki) and S. obassia Siebold et Zucc. (Haku'unboku) throughout Japan (Kobayashi et al 1998;Nakashima 2001 Katsuki and Kobayashi, Trans Mycol Soc Jpn 16:10, 1975.…”
Section: Pseudocercospora Hachijokibushimentioning
confidence: 99%